2023
DOI: 10.3389/fcell.2023.1173235
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyroptosis in inflammatory diseases

Abstract: Programmed cell death has crucial roles in the physiological maturation of an organism, the maintenance of metabolism, and disease progression. Pyroptosis, a form of programmed cell death which has recently received much attention, is closely related to inflammation and occurs via canonical, non-canonical, caspase-3-dependent, and unclassified pathways. The pore-forming gasdermin proteins mediate pyroptosis by promoting cell lysis, contributing to the outflow of large amounts of inflammatory cytokines and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 194 publications
0
5
0
Order By: Relevance
“…Previous studies reported lysosomal membrane permeabilization by iron and leakage of cathepsin D as an inducer of necrotic cell death 39 and release of cathepsin B into the cytosol as an activator of pyroptosis 40 . Traditionally incited by pathogen-associated molecular patterns (PAMPs), pyroptosis can also be spurred by elevated levels of ROS and lysosomal rupture 41, 42 . Remarkably, our observations regarding the activation of caspase 1 and the concomitant presence of inactive caspase 3 in fibroblasts subjected to lipofuscin treatment in combination with lysosomal rupture and elevated ROS concentrations, closely align with the early phase of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported lysosomal membrane permeabilization by iron and leakage of cathepsin D as an inducer of necrotic cell death 39 and release of cathepsin B into the cytosol as an activator of pyroptosis 40 . Traditionally incited by pathogen-associated molecular patterns (PAMPs), pyroptosis can also be spurred by elevated levels of ROS and lysosomal rupture 41, 42 . Remarkably, our observations regarding the activation of caspase 1 and the concomitant presence of inactive caspase 3 in fibroblasts subjected to lipofuscin treatment in combination with lysosomal rupture and elevated ROS concentrations, closely align with the early phase of pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The broad-range increases in cytokines could be the consequence of pyroptosis pathway activation or independence. Interleukins, TNF cytokines, and c-c and c-x chemokines could be released as part of an inflammatory response triggered by pyroptotic cell death [62][63][64][65]. Inhibiting TNF-α by CC-5013 has been shown to suppress pyroptosis signaling in the liver and kidneys through a caspase-1 independent pathway [66].…”
Section: Discussionmentioning
confidence: 99%
“…LRR has been involved in ligand-sensing and autoregulation. All three domains are involved in the protein interaction networks ( 7 ).…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…NLRP3 is known to respond to a variety of stimuli, including PAMPs, DAMPs and bacterial toxins. These PAMPs include fungi, such as Candida albicans and Saccharomyces cerevisiae ( 23 ); bacteria, including Staphylococcus aureus (S. aureus), Listeria monocytogenes and Neisseria gonorrhoeae ( 24 26 ); and viruses, such as Sendai, influenza, encephalomyocarditis viruses and adenovirus ( 7 , 27 29 ). In addition, several host-derived molecules, which are indicative of cellular injury or stress can also activate the NLRP3 inflammasome, including ATP released from necrotic cells, hyaluronan, glucose, monosodium urate, myeloid-β, skin irritants, imidazoquinoline compounds, silica, asbestos and alum ( Fig.…”
Section: Activation and Regulation Of The Nlrp3 Inflammasomementioning
confidence: 99%